A review of challenges and security risks of cloud computing - Hussam Alddin S., Ahmed; Mohammed Hasan, Ali; Laith M., Kadhum; Mohamad Fadli, Zolkipli; Yazan A., Alsariera (UTEM, 2017)
Cloud computing has been an attention in the new era of the IT technologies as there is an increase demand in the services or utility computing all over the wide world web. Security risk resulting from resource sharing throughout the cloud computing becomes one of the most challenging concerns in providing powerful processing and storage as on-demand services. Taking the advantage of low cost derived from the increase in efficiency and performance facilitated by cloud computing, governments and organizations around the globe are motivated to build or migrate to the cloud. However, there are still many technical issues relating to the features of cloud computing and the provision of quality service, leading to a delay in adopting cloud computing. This review paper highlights the security risks and challenges of cloud computing and study the security requirements for cloud computing. The primary aim of this review is to classify the security risks and challenges related to the different forms of cloud computing (SaaS, PaaS and IaaS).